The role and importance of rare earth elements as dopants for hydroxyapatite structure: a comprehensive review - Kareem, Rebaz Obaid; Mahmood, Bahroz Kareem; Barzinjy, Azeez A.; Bulut, Niyazi; Kaygili, Omer; Keser, Serhat; Ates, Tankut (Elsevier, 2025)
This comprehensive review delves into the significance of rare earth elements (REEs) as dopants in hydroxyapatite (HAp) structures, highlighting their role in modulating the material's crystallinity, solubility, and bioactivity. The unique properties of REEs, such as their ability to form ionic bonds with hydroxyapatite, are discussed in relation to their impact on the material's interactions with biological molecules. The review also examines the effects of REE doping on the in vitro and in vivo behavior of HAp, including its influence on cell proliferation, differentiation, and mineralization. Furthermore, the potential applications of REE-doped HAp in orthopedic and dental implants, as well as its potential in bone tissue engineering, are explored. This review provides a thorough understanding of the role and importance of REEs as dopants in HAp structures, shedding light on their potential to revolutionize the development of biomaterials for biomedical applications, especially in bone tissues engineering.
Keywords: Hydroxyapatite; Rare earth elements; Solubility; Bone tissues engineering; Bioactivity